Mapping the Distinctive Populations of Lymphatic Endothelial Cells in Different Zones of Human Lymph Nodes - Park, Saem Mul (Public Library of Science, 2014)
The lymphatic sinuses in human lymph nodes (LNs) are crucial to LN function yet their structure remains poorly defined. Much of our current knowledge of lymphatic sinuses derives from rodent models, however human LNs differ substantially in their sinus structure, most notably due to the presence of trabeculae and trabecular lymphatic sinuses that rodent LNs lack. Lymphatic sinuses are bounded and traversed by lymphatic endothelial cells (LECs). A better understanding of LECs in human LNs is likely to improve our understanding of the regulation of cell trafficking within LNs, now an important therapeutic target, as well as disease processes that involve lymphatic sinuses. We therefore sought to map all the LECs within human LNs using multicolor immunofluorescence microscopy to visualize the distribution of a range of putative markers. PROX1 was the only marker that uniquely identified the LECs lining and traversing all the sinuses in human LNs. In contrast, LYVE1 and STAB2 were only expressed by LECs in the paracortical and medullary sinuses in the vast majority of LNs studied, whilst the subcapsular and trabecular sinuses lacked these molecules. These data highlight the existence of at least two distinctive populations of LECs within human LNs. Of the other LEC markers, we confirmed VEGFR3 was not specific for LECs, and CD144 and CD31 stained both LECs and blood vascular endothelial cells (BECs); in contrast, CD59 and CD105 stained BECs but not LECs. We also showed that antigen-presenting cells (APCs) in the sinuses could be clearly distinguished from LECs by their expression of CD169, and their lack of expression of PROX1 and STAB2, or endothelial markers such as CD144. However, both LECs and sinus APCs were stained with DCN46, an antibody commonly used to detect CD209.